Comparative Study of HIV/AIDS Prevention Behaviors between Students in Schools that Do Not and Have PIK-R - Eva Nurfadila; Sri Hartati Pratiwi; Siti Ulfah Rifa'atul Fitri (Indonesian Journal of Global Health Research, 2024)
The Youth Information and Counseling Center (PIK-R) was formed with the aim of forming healthy behavior in teenagers to prevent an increase in the number of HIV/AIDS cases. Currently, there has been no comparative research on HIV/AIDS prevention behavior in schools that do not and do not have PIK-R. This research aims to see differences in HIV/AIDS prevention behavior between students in schools that do not and have PIK-R. This research method is descriptive comparative with a cross sectional time approach. Respondents were students of SMA Negeri 1 Pangandaran and SMK Negeri 1 Pangandaran with a sample of 95 people using the stratified sampling method. The instrument used is the Indonesian version of the Sexual Behavioral Abstine HIV/AIDS Questionnaire (SBAHAQ) which has been declared valid and reliable with a mean CVI value of 0.96 and Cronbach's Alpha values of 0.87, 0.77 and 0.85. Data analysis uses univariate and bivariate analysis. The results of the comparative test with the Mann Whitney Test obtained an asymp sig (2-tailed) value of 0.331 (>0.05). Based on the research results, it can be concluded that there is no significant difference between HIV/AIDS prevention behavior among students in schools with and without PIK-R.